Green and Black Cardamom in a Diet-Induced Rat Model of Metabolic Syndrome - Maharshi Bhaswant (Nutrients, 2015)
Both black (B) and green (G) cardamom are used as flavours during food preparation. This study investigated the responses to B and G in a diet-induced rat model of human metabolic syndrome. Male Wistar rats were fed either a corn starch-rich diet (C) or a high-carbohydrate, high-fat diet with increased simple sugars along with saturated and trans fats (H) for 16 weeks. H rats showed signs of metabolic syndrome leading to visceral obesity with hypertension, glucose intolerance, cardiovascular remodelling and nonalcoholic fatty liver disease. Food was supplemented with 3% dried B or G for the final eight weeks only. The major volatile components were the closely related terpenes, 1,8-cineole in B and α-terpinyl acetate in G. HB (high-carbohydrate, high-fat + black cardamom) rats showed marked reversal of diet-induced changes, with decreased visceral adiposity, total body fat mass, systolic blood pressure and plasma triglycerides, and structure and function of the heart and liver. In contrast, HG (high-carbohydrate, high-fat + green cardamom) rats increased visceral adiposity and total body fat mass, and increased heart and liver damage, without consistent improvement in the signs of metabolic syndrome. These results suggest that black cardamom is more effective in reversing the signs of metabolic syndrome than green cardamom.